Far Eastern tour : the Canadian infantry in Korea, 1950-1953 - Watson, Brent Byron, 1970- (McGill-Queen's University Press, 2002)
What was it like to serve in the infantry during Canada's "Forgotten War"? In Far Eastern Tour Brent Watson tells the story of the Korean War from the perspective of Canadian soldiers. Dealing with the fiasco surrounding recruitment, a training regime inappropriate for the war they were to fight, and the stark living and combat conditions the soldiers faced, Watson examines the human consequences of an Army that was totally unprepared for service in the Far East. Using rigorous archival research and oral accounts, Far Eastern Tour follows the experiences of Canadian soldiers from the time they responded to the government's call to arms to their indifferent homecoming a year later. Because Army brass and defence planners in Ottawa insisted on viewing the conflict through the familiar lens of the Canadian Army's World War II experiences in Europe, Canadian soldiers in Korea suffered needless casualties and endured conditions that bordered on criminal neglect. That Canadian troops "soldiered on" in spite of such hardship and misery was a measure of their fortitude and dedication.